2007
DOI: 10.1016/j.nbd.2006.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of mitochondrial permeability transition as a primary neuroprotective target of minocycline

Abstract: Minocycline has been shown to be neuroprotective in ischemic and neurodegenerative disease models and could potentially be relevant for clinical use. We revisited the hypothesis that minocycline acts through direct inhibition of calcium-induced mitochondrial permeability transition (mPT) resulting in reduced release of cytochrome c (cyt c). Minocycline, at high dosage, was found to prevent calcium-induced mitochondrial swelling under energized conditions similarly to the mPT inhibitor cyclosporin A (CsA) in ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 47 publications
5
35
0
Order By: Relevance
“…The ability of MC to inhibit the formation of mPTP was also reported from groups focusing on isolated brain and liver mitochondria [2,43]. In contrast, Mansson et al did not show a direct inhibition of the mPTP in isolated brain mitochondria [25]. To clarify this issue, we measured single-channel currents through the mPTP of mitoplasts.…”
Section: +mentioning
confidence: 65%
See 1 more Smart Citation
“…The ability of MC to inhibit the formation of mPTP was also reported from groups focusing on isolated brain and liver mitochondria [2,43]. In contrast, Mansson et al did not show a direct inhibition of the mPTP in isolated brain mitochondria [25]. To clarify this issue, we measured single-channel currents through the mPTP of mitoplasts.…”
Section: +mentioning
confidence: 65%
“…In addition, the MC-mediated neuroprotection is associated with a blockade of caspases, inhibition of MAP kinase, and prevention of cytochrome c release [2,5,14,24]. But, a direct involvement of MC in mitochondrial permeability transition is still a matter of debate [25].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium uptake into the mitochondrial matrix space is a necessary step for the Ca 2ϩ -induced MPT, and calcium uptake inhibitors such as ruthenium red potently block the MPT. 31,32 Simultaneous treatment with minocycline and NIM811 did not confer additional protection against the MPT in isolated mitochondria beyond either agent alone (data not shown). Respiratory measurements in mitochondria showed that inhibition of mitochondrial Ca 2ϩ uptake by minocycline was not attributable to respiratory inhibition or uncoupling, because ADP-stimulated state 3 respiration and ADP/O and Ca 2ϩ /O ratios were not changed with as much as 50 M minocycline (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…One proposed mechanism is modulation of the mitochondrial permeability transition (mPT), a Ca 2ϩ -dependent pathogenic event leading to necrotic and/or apoptotic cell death. [1][2][3][4][5] A recent study in HEPATOLOGY by Theruvath et al, 6 investigating storage/ reperfusion injury following rat liver transplantation, concluded that minocycline prevented mPT and mitigated liver injury by decreasing mitochondrial Ca 2ϩ uptake without affecting mitochondrial respiration. Further, the authors argue that it could be consistent with clinical practice to (pre)treat stored livers and graft recipients with minocycline.…”
mentioning
confidence: 99%
“…We argue that minocycline at moderate to high dosing, similar to what we have shown in brain mitochondria, prevents Ca 2ϩ -uptake and mPT-induced swelling by respiratory inhibition. 1,5 Further, depending on the buffer system used, the decreased Ca 2ϩ retention can be explained by minocycline-induced increase of mPT sensitivity related to (1) inhibited respiration 1,5 and (2) chelating of Mg 2ϩ , 8 or (3) direct activation of mPT (even during concurrent cyclosporin A treatment) by adding Ca 2ϩ or in Ca 2ϩ loaded mitochondria, as recently shown by Kupsch et al 8 To stringently evaluate effects of minocycline during the process of Ca 2ϩ uptake, retention, and mPT, mitochondrial oxygen consumption can be monitored during a continuous Ca 2ϩ infusion (Fig. 1A,B).…”
mentioning
confidence: 99%